Factors affecting students' ability to respond to literacy text as a form of higher order thinking skills / Siti Sarah Abdur Rani - Abdur Rani, Siti Sarah (2013)
This study aims to investigate secondary school students’ ability to perform higher order thinking skills through relating their personal experiences and ideas and what affects the students’ ability to do so. There are four research objectives; i) to examine students’ ability to relate their personal experiences or ideas to the literary text, ii) to examine how teaching method employed in the classroom is related to the students’ ability to relate their personal experiences and ideas to the literary text, iii) to examine how the students’ interest in literature is related to their ability to reflect their personal experiences and ideas to the text, and iv) to examine how the students’ attitude towards learning literature is related to their ability to reflect their personal experiences and ideas to the text. This research employed a mixed method design with a total of 131 secondary school students selected as the sample of this study. The instruments used were surveys and Reader Response semi-structured questions. The findings revealed that the majority of students were unable to relate with the literary text in a deep and meaningful way and students’ interest is the only factor that plays a role in it. Furthermore, English literature lessons focus heavily on the language and content aspect of the literature component. The study via the findings, hopes to improve the teaching of the English literature component in secondary school so as to produce students with high order thinking skills.